Development of test kit for detection of rifampin resistance in mycobacterium tuberculosis by PCR-reverse line blot hybridization - Somying Tumwasorn (Faculty of Medicine, Chulalongkorn University, 2010)
A genetic test by PCR-reverse line blot hybridization was developed for rapid detection of mycobacterium tuberculosis and rifampin resistance simultaneously. Duplex PCR targeting IS 6110 and rpoB gene was employed to detect M. tuberculosis and the rpoB fragment with rifampin resistance hot spot region. The analytical sensitivity of duplex PCR for IS 6110 and rpoB gene was found to be 10 and 100fg of M.Tuberculosis H37Rv DNA, respectively. Since duplex PCR was specific to M. tuberculosis complex, it was thus able to be applied directly in clinical specimens. Oligonucleotide probes were designed to detect wild-type and mutant genotypes of rpoB gene. These probes together with an M. tuberculosis specific probe were blotted in parallel lines in a membrane strip and used for hybridization with PCR product amplified from clinical isolates and sputum specimens. The developed test was able to detect M. tuberculosis clinical isolates with known rpoB gene sequences and the presence of M. tuberculosis in 98.75% (79/80) of sputum specimens. When the amplified products were subjected to reverse line blot hybridization, the test detected 85.71% (24/28) of rifampin-resistant and all rifampin sensitive M. tuberculosis in sputums specimens. The clinical sensitivity and specificity of the test for rifampin resistance was 85.7% and 100%, respectively. Considering the turnaround time, cost and shelf life of the test, duplex PCR-reverse line blot hybridization offers a potential of the test kit for detection of frequent mutations leading to rifampin resistance in clinical laboratories.